1936
DOI: 10.1098/rspb.1936.0070
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fumarate on respiration

Abstract: In t r o d u c t io n

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1939
1939
1991
1991

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(3 citation statements)
references
References 2 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…In attempting to design further experiments to clarify the nature of this difference. we were reminded of the catalytic "sparking" effect of fumarate in isolated tissues oxidizing pyruvate (14,15). We wondered whether fumarate could exert a similar catalytic effect on malate reabsorption by "sparking" the oxidative energy production in the renal tubular cells.…”
Section: Methodsmentioning
confidence: 99%
“…In attempting to design further experiments to clarify the nature of this difference. we were reminded of the catalytic "sparking" effect of fumarate in isolated tissues oxidizing pyruvate (14,15). We wondered whether fumarate could exert a similar catalytic effect on malate reabsorption by "sparking" the oxidative energy production in the renal tubular cells.…”
Section: Methodsmentioning
confidence: 99%
“…We found that the oxygen uptake of these tissues was increased by the addition of very small amounts of fumarate and that this increase was much more than could be accounted for by the oxidation of the fumarate itself. Substances that yielded fumarate on contact with tissues, such as succinate, malate, oxaloacetate, had a similar action (35).…”
mentioning
confidence: 92%
“…At the end of three years of study in Europe, I returned to the University of Wisconsin as a research associate in biochemistry at the Bowman Cancer Research Institute, later to be renamed the McArdle Cancer Institute. Here, I continued research on tissue respiration with Carl Baumann who had also returned to Wisconsin (35).…”
mentioning
confidence: 99%